Program Edukasi Joint Protection Technique Pada Aktivitas Ibu Rumah Tangga - Aniek Puspitosari (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: Housewives are synonymous with household chores. These activities are carried out regularly, such as washing clothes, cooking, shopping, sweeping floors, washing dishes, cleaning the house. Housewives also carry out regular activities such as mopping, ironing, sweeping the yard, and gardening. Intensive activities and inappropriate positions performed by housewives have the potential to cause musculoskeletal complaints in the upper extremities such as pain or tingling sensation. Efforts that can be made to reduce these complaints are counseling on the application of the Joint Protection Technique (JPT). JPT aims to reduce pain and improve joint function through the use of an ergonomic approach such as changing movement patterns, modifying tasks and the environment. After participating in extension activities, it is hoped that housewives will be able to apply JPT in household activities without musculoskeletal complaints. Methods: Health education was carried out by distributing leaflets via the WhatApps group, lecturing on explaining images printed on leaflets and demonstrating the application of JPT in housekeeping activities. The counseling participants were housewives in RW 8, Kebakkalang, Kemiri Village, Kebakkramat District. The counseling activity took place at the house of one of the residents using equipment such as brooms, buckets of water, clothes, grocery bags, irons, and cooking utensils. Results: Counseling activities were carried out during March 2021 with 16 housewives as participants. Counseling activities still pay attention to health protocols, namely maintaining distance and wearing masks. Participants are able to demonstrate directly the application of the JPT principles in the activities of sweeping, washing clothes, shopping for vegetables, ironing, and cooking with real household context and equipment. Conclusion: Domestic work that is carried out by applying the JPT principle can be carried out without reducing the quality of the work, making the work stages simpler and not causing fatigue.